2007
DOI: 10.1152/ajplung.00140.2007
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics of silencing TREM-1 on TLR4 signaling in macrophages

Abstract: Triggering receptor expressed on myeloid cells 1 (TREM-1) is a recently discovered molecule that is expressed on the cell surface of monocytes and neutrophils. Engagement of TREM-1 triggers synthesis of proinflammatory cytokines in response to microbes, but the extent and mechanism by which TREM-1 modulates the inflammatory response is poorly defined. In the present study, we investigated the functional effects of blocking TREM-1 on the Toll-like receptor (TLR)4-mediated signaling pathway in macrophages. By tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
99
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 36 publications
10
99
0
2
Order By: Relevance
“…We have shown that silencing of TREM-1 gene significantly altered expression of several genes, including MyD88, CD14, IkBa, IL-1b, MCP-1, and IL-10 in response to treatment with LPS in macrophage [24,25]. Thus, it is evident that TREM-1 may amplify the responses of both TLR and NLR in response to microbial products.…”
mentioning
confidence: 92%
“…We have shown that silencing of TREM-1 gene significantly altered expression of several genes, including MyD88, CD14, IkBa, IL-1b, MCP-1, and IL-10 in response to treatment with LPS in macrophage [24,25]. Thus, it is evident that TREM-1 may amplify the responses of both TLR and NLR in response to microbial products.…”
mentioning
confidence: 92%
“…A crucial role of TREM-1 has initially been demonstrated in the development of septic shock (Bouchon et al, 2001;Gibot et al, 2004b). TREM-1 activation and expression occurs synergistically with TLRs (Arts et al, 2011;Klesney-Tait and Colonna, 2007;Klesney-Tait et al, 2006), as the TREM family contains both inhibitory and activating receptors capable of modulating the signaling downstream of TLRs (Allcock et al, 2003;Ornatowska et al, 2007). Moreover, TREM-1 has also been associated with NOD-Like Receptors (NLR), responsible for sensing microbial danger signals and amplifying the inflammatory response (El Mezayen et al, 2007;Netea et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Following ligation it associates with a signal transduction molecule, DAP12, triggering that initiates the secretion of inflammatory cytokines. TREM-1 has emerged as an important amplifier of TLR-in- duced inflammatory responses activating transcription factors that regulate the expression of proinflammatory cytokines and chemokines (14,16). This study provides yet another mechanism by which TREM-1 can perpetuate inflammation by inhibiting apoptosis of macrophage by activating the key anti-apoptotic proteins of the Bcl-2 family.…”
Section: Discussionmentioning
confidence: 87%
“…We have shown that the functional consequences of TREM-1 silencing in macrophages include an altered availability of key signaling (CD14, IB␣, and MyD88), and effector molecules (MCP-1, IL-1␤, and IL-6) downstream of TLR activation. Furthermore, the presence of TLRs is necessary for the expression of TREM-1 in response to specific TLR ligands (15)(16)(17). These receptors have thus emerged as potent amplifiers of TLR-initiated inflammatory responses (14,16,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation